(untitled) (Globalization and Business, 2018)
The scientific article represents the review of the following aspects: audit organization and ways of its improvement; the essence of the audit, goals, the role and importance in market economy; audit basics, regulations and development prospects in Georgia as well as the audit experience in foreign countries. The significant place is given to organizational issues of audit, there are also presented the procedures for making an audit conclusion, its structure, form, content and status. It is also considered the next stage of completion of the audit -the review of the audit conclusion (act, recognition), the appeal process, response forms and legal aspects of the results revealed. It is argued in the paper if the development of audit activities will help entrepreneurial subjects to make decisions that are justified for improvement of management processes and financial conditions. Besides, development of audit activities is necessary to ensure the state interests of courts, prosecutors and investigators. The work was aimed at presenting the perspectives of necessity and development of audit activities in modern conditions which have been achieved in accordance with the nrequirements and volumes of bachelor›s work.